An investigation about effects of fluid-structure-soil interaction on response modification coefficient of elevated concrete tanks. Issue 1 (2nd January 2016) - Hashemi, Mirtaha; Bargi, Khosrow
Abstract: This paper aims to observe effects of fluid-structure-soil interactions on the response modification coefficient of elevated concrete tanks with frame and shaft supporting systems. Because of weaknesses and failures of elevated tanks that have been reported in recent earthquakes and importance of optimum and resistant design and also better seismic performance of these structures, it is essential to investigate on the response modification coefficient of elevated concrete tanks. In this paper, the response modification coefficient has been evaluated by using the numerical modeling. The method of research is a case study. The models have been subjected to an ensemble of important earthquake ground motions. The effects of soilstructure interactions and fluid-structure interactions on seismic behavior of the elevated concrete tanks have been modeled by the equivalent springs and Housner's method, respectively. Dynamic response of the elevated tanks has been considered by using the nonlinear time history analysis and the discrete plastic hinge approach. Finally, the effects of fluid-structure-soil interactions on the response modification coefficient of the elevated concrete tanks have been discussed by considering results of the analyses. It has been concluded that the codes may underestimate base seismic forces for some seismic regions and some subsoil classes.